Intelligence-Led Policing To Reduce The Vulnerability Of Commercial Sex Workers Online In The Central Jakarta Metro Police Area - Buwono, Arif Ardian Eka; Runturambi, Arthur Josias Simon; Daryanto, Eko (GoAcademica Research & Publishing, 2024)
Various studies show that the crime rate against Commercial Sex Workers is very high. However, official data often shows that crimes against Commercial Sex Workers are low. This phenomenon was also found in the Central Jakarta Metro Police area. Various vulnerabilities that afflict Commercial Sex Workers in the region have been found. The evaluation was conducted to measure awareness of protection against commercial sex workers by members of the Central Jakarta Metro Police, identify reasons for underreporting of crimes by online sex workers, assess protection against online commercial sex workers, and the involvement of commercial sex workers in law enforcement. This study uses an intelligence-led policing approach based on intelligence analysis with a qualitative approach. The results show that increasing awareness of protection is still very much needed in the Central Jakarta Metro Police environment. In addition, there are still obstacles to reporting crimes by commercial sex workers. Protection against online sex workers needs to be improved, but it needs to be supported by better cooperation. It is recommended to continue to evaluate and enhance weaknesses to improve the response and protection of online sex workers.